Optimizing the Circulation of Islamic Boarding School MSME Funds Through Digital-Based Sharia Microfinance Technology Innovation at the Nurul Jadid Islamic Boarding School, Paiton - Ahmad Zaenal Abidin; Mohammad Alief Hidayatullah (Yayasan Pendidikan Bustanul Ulum Mojokerto, 2026)
This study examines the role of digital-based Islamic microfinance technology in supporting the circulation of funds among Islamic boarding school (pesantren) MSMEs at the Nurul Jadid Islamic Boarding School in Paiton. The research employed a qualitative descriptive approach with a case study design. Data were collected through interviews, observations, and documentation with MSME managers, Islamic boarding school cooperative administrators, and students using digital financial services. The results indicate that utilizing digital financial systems helps accelerate transactions, organize financial records more efficiently, increase transparency, and promote efficient management of Islamic boarding school MSME funds. However, its implementation still faces challenges such as uneven digital literacy, varying user capabilities, and inadequate infrastructure support. Therefore, digital-based Islamic microfinance technology has the potential to become a means of strengthening a more modern, orderly, and sustainable Islamic boarding school economy.